Pelatihan Pengelolaan Kegiatan Keagamaan Berbasis Masjid oleh Mahasiswa KKN Tematik di Desa Mekar Sari Ilir Talo Seluma - Peri Pernandes; Amelia Sarina; Doni Aditya Putra; Triea Agustini (Yayasan Darussalam Bengkulu, 2025)
This study aims to describe the process and impact of mosque-based religious activity management training carried out by Thematic Community Service (KKN) students in Mekar Sari Village, Ilir Talo District, Seluma Regency. The main problem faced by the village community is the suboptimal function of the mosque as a center for religious activities, especially in terms of managerial aspects and participation of the younger generation. With a qualitative approach and field study method, this study describes interventions in the form of mosque management training, the formation of mosque youth, and the systematic preparation of religious agendas. The results of the study showed a significant increase in the management of religious activities, increased community involvement, especially youth, and the transformation of mosques as centers of spiritual and social activities. This training is also considered to have the potential for replication in other villages with similar conditions. These findings indicate that Thematic KKN based on community empowerment through mosques can be an effective strategy in supporting development based on Islamic values.